2021
DOI: 10.1101/2021.01.12.426396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression of a fungal lectin in Arabidopsis enhances plant growth and resistance towards microbial pathogens and plant-parasitic nematode

Abstract: Coprinopsis cinerea lectin 2 (CCL2) is a fucoside-binding lectin from the basidiomycete C. cinerea that is toxic to the bacterivorous nematode Caenorhabditis elegans as well as animal-parasitic and fungivorous nematodes. We expressed CCL2 in Arabidopsis to assess its protective potential towards plant-parasitic nematodes. Our results demonstrate that expression of CCL2 enhances host resistance against the cyst nematode Heterodera schachtii. Surprisingly, CCL2-expressing plants were also more resistant to funga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Such interplay between sugar signaling events (translating the cellular energy levels) and glycosylation might be important to balance the rate of glycosylation with the current sugar status. Another interesting study showed that expression of the Coprinopsis cinerea lectin 2 (CCL2), a fucoside-binding lectin from Botrytis cinerea in Arabidopsis, enhanced growth and disease resistance against a variety of pathogens [465]. When the carbohydrate binding ability of CCL2 was disturbed, disease tolerance is abolished, suggesting that carbohydrate interaction is required for induced tolerance.…”
Section: Interplay Between Sugar Signaling and Glycoconjugatesmentioning
confidence: 99%
“…Such interplay between sugar signaling events (translating the cellular energy levels) and glycosylation might be important to balance the rate of glycosylation with the current sugar status. Another interesting study showed that expression of the Coprinopsis cinerea lectin 2 (CCL2), a fucoside-binding lectin from Botrytis cinerea in Arabidopsis, enhanced growth and disease resistance against a variety of pathogens [465]. When the carbohydrate binding ability of CCL2 was disturbed, disease tolerance is abolished, suggesting that carbohydrate interaction is required for induced tolerance.…”
Section: Interplay Between Sugar Signaling and Glycoconjugatesmentioning
confidence: 99%